Intellectual Capital and Firm Performance in ASEAN: The Role of Research and Development - Bima Cinintya Pratama; Hardiyanto Wibowo; Maulida Nurul Innayah (Journal of Accounting and Investment, 2019)
This paper aims to investigate the association between intellectual capital, research and development, and firm financial performance in an emerging market context, which is ASEAN. The effect of Intellectual Capital and Research and Development Intensity towards firm financial performance is examined while testing the moderating role of research and development on the relationship between intellectual capital and firm financial performance. Panel data regression model analysis is used for a sample of non-financial companies in ASEAN countries, namely Indonesia, Malaysia, Philippines, and Singapore during 2015-2017. The final sample used in this study consists of a total of 383 observations. The results showed that intellectual capital has a positive effect on firm financial performance. This result indicates that intellectual capital can generate higher financial performance for the firms. A similar result also found in the relationship between research and development intensity and firm financial performance. Meanwhile, research and development are proved to be able to moderate the positive relationship between intellectual capital and firm financial performance. This result means that if the companies could facilitate their intellectual capital by giving more intensity of research and development, intellectual capital will be generated even more performance for the firms. This result implies that firms should utilize and maintain intellectual capital together with research and development